Analysis of English Language Learning Strategies for Early Childhood through Music and Movement Approach at Mighty Minds Preschool - Habibur Rachman; Yon A.E; Lenny Solo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Teaching English to young children plays a crucial role in shaping their language development and laying a solid foundation for future learning. Early mastery of English provides children with long-term advantages that influence both academic success and professional opportunities. Scholars and educational institutions recognize early childhood as a critical period for cognitive and linguistic growth, which makes the selection of effective teaching strategies essential. This study explores the integration of music and movement as strategies for teaching English to preschool learners. The use of rhythm, melody, and physical activity in the classroom is expected to create a multisensory learning environment that caters to diverse learning styles. Previous studies, such as Lestari (2019), have demonstrated that combining songs with movement significantly enhances vocabulary acquisition in preschool-aged children. Additionally, kinesthetic learning activities have been shown to improve comprehension and memory through active engagement. This approach is aligned with the Direktorat PAUD (2015) guidelines, which emphasize a holistic model of early childhood education that integrates cognitive, emotional, and physical development. By examining the role of music and movement in the classroom at Mighty Minds Preschool, this study aims to highlight how these strategies contribute to vocabulary growth, emotional engagement, and classroom interaction. The findings are anticipated to provide valuable insights into innovative pedagogical methods that can enhance English learning in early childhood education